Conceptualising private client behaviour within the professional service relationship - Hilton, Toni (2004)
This study, which seeks to conceptualise client behaviours within the professional service relationship is located within the academic literature associated with relationship marketing. However, this study differs from the main characteristics of that literature in two ways.